2010
DOI: 10.1118/1.3480965
|View full text |Cite
|
Sign up to set email alerts
|

Radiation dose estimation using preclinical imaging with ‐metaiodobenzylguanidine (MIBG) PET

Abstract: The authors estimated human-equivalent internal radiation dose of 124I-MIBG using preclinical imaging data. As a reference, the effective dose estimation showed that 124I-MIBG would deliver less radiation dose than 124I-NaI, a radiotracer already being used in patients with thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 31 publications
(20 reference statements)
5
32
0
Order By: Relevance
“…In this study we have used 5 animals per tracer, analyzed at three time-points. This are in agreement with other studies were the number of animals per time point typically are between 3-6, with the number of time points between 3 and 7 [20,21,26,27]. Despite the relatively low number of data points in this study (1, 4.5 and 22 h) it seems that three data points are sufficient considering the relatively high concordance between predicted and observed total body dosimetry values for 64 Cu-DOTA-TATE (Fig.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study we have used 5 animals per tracer, analyzed at three time-points. This are in agreement with other studies were the number of animals per time point typically are between 3-6, with the number of time points between 3 and 7 [20,21,26,27]. Despite the relatively low number of data points in this study (1, 4.5 and 22 h) it seems that three data points are sufficient considering the relatively high concordance between predicted and observed total body dosimetry values for 64 Cu-DOTA-TATE (Fig.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the obvious differences in anatomy and physiology between mice and man, relatively close correlation between predicted vs. observed dosimetry have however been found, exemplified by close predictions of 4 out of 6 PET tracers in the study by Sakata and co-workers [22]. Moreover, recently two studies have reported the use of PET image-derived biodistribution analysis in mice for use to estimate human dosimetry [26,27]. Importantly, a significant correlation between conventional biodistribution tissue analysis and image-derived analysis were reported (p = 0.9666), thus validating this new approach [27].…”
Section: Introductionmentioning
confidence: 89%
“…This is likely due to differences in tumor perfusion, proportion of viable tumor cells, biologic body clearance rate, and tumor avidity and retention of MIBG. Perhaps improving the accuracy of the dosimetry with SPECT (22) or using 124 I-MIBG with PET would increase correlation between activity and response (23). Overall, the measurable tumors all received significant doses, with a median tumor dose of 49 Gy, more than twice the standard dose applied currently by external-beam radiation for newly diagnosed patients with high-risk disease (24).…”
Section: Discussionmentioning
confidence: 99%
“…Pretherapeutic imaging to estimate disease distribution and burden is possible with high sensitivity in both neuroblastoma and PHEO patients (48,49). Radiation dosimetry predicted from animal data was favorable, with mean effective doses ranging from 0.34 mSv/MBq for adults to 1.9-3.75 for children 1 y old or younger (135). In a preclinical xenograft model for neuroblastoma, the radiation dose in tumors and organs was determined.…”
Section: Strategies For Improving Net Targeting and Dose Delivery Witmentioning
confidence: 99%